2019
DOI: 10.33258/birle.v2i4.516
|View full text |Cite
|
Sign up to set email alerts
|

Development of Web-Based Learning Media on Social Studies Subject at Junior High School Methodist Lubuk Pakam, Indonesia

Abstract: Prioritizing WEB-based knowledge learning. The approach taken to familiarize students with high-level thinking is helped by WEB. Based on preliminary analysis, it is known that teachers have difficulties in designing a WEB-based social science learning media. This study uses the ADDIE model to develop web-based learning media. The development research flow, namely, analysis, design, development, implementation, and evaluation. The results of research in the form of WEB-based social studies learning media produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Additionally, assessment tools, such as digital literacy and critical thinking pretest and post-test questions, were created and customized to the material and psychological development stages of the students. The results of this stage supported the notion that the ADDIE model's design activities are methodical, beginning with the product's concept and content design and ending with comprehensive implementation guidelines (Thesalonika et al, 2019;Samsudin et al, 2021).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Additionally, assessment tools, such as digital literacy and critical thinking pretest and post-test questions, were created and customized to the material and psychological development stages of the students. The results of this stage supported the notion that the ADDIE model's design activities are methodical, beginning with the product's concept and content design and ending with comprehensive implementation guidelines (Thesalonika et al, 2019;Samsudin et al, 2021).…”
Section: Resultssupporting
confidence: 59%
“…This aligns with Salas-Rueda et al ( 2020), who noted that the analysis stage of the ADDIE model should focus on assessing student needs, analyzing problems, and task analysis to identify gaps, define student needs, and develop task-oriented solutions. Thesalonika et al (2019) also emphasized that development research starts with addressing issues that already exist, such as out-of-date products or ones that no longer satisfy the needs of the target audience, considering factors like learning environment, technology, and student characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study that is related in term of similarity to this research conducted by Thesalonika et al (2019) in her study entitled "Development of Web-Based Learning Media on Social Studies Subject at Junior High School Methodist Lubuk Pakam, Indonesia" showed that web-based learning is feasible to be used on teaching and learning. The study also showed that the use of webbased learning media can improve students' comprehension on the material being taught.…”
Section: Introductionmentioning
confidence: 70%
“…The research results were in line with the theory of Salas-Rueda et al ( 2020), which stated that the stages of the ADDIE model analysis analyze students in terms of their needs, problem analysis, and task analysis so that the output of this analysis process is in the form of student characteristics, gap identification, identification of needs and analysis of tasks in the form of solutions to their needs. Trust & Pektas (2018) and Thesalonika et al (2019) also states that development research departs from existing problems such as current or available products that are no longer relevant to the needs of the target, learning environment, technology, student characteristics, and so on.…”
Section: Resultsmentioning
confidence: 99%
“…Instructions for implementing the design or manufacture of products were sought to be written clearly and in detail. At this stage, the product design was still conceptual and underlie the development process at the next stage (Thesalonika et al, 2019;Samsudin et al, 2021;Ngussa, 2014).…”
Section: Resultsmentioning
confidence: 99%